1990
DOI: 10.1007/3-540-52791-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of filled polymers

Abstract: A l e x a n d e r Y. M a l k i n Research Institute o f Plastics, Perovskii proezd 35, U S S R 111 112, M o s c o w E-112, U S S R Published data, concerning the results of measuring rheological properties of polymer melts with rigid fillers, are discussed. The review is based mainly on the works of the 1980s. The effect of a filler's presence on three fundamental parameters of a material, namely yield stress, viscosity, and rubbery elasticity is considered. The analysis is based essentially on qualitative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Early work on polymer solutions by Highgate and Whorlow [39] first suggested that relative fluidities of suspensions could be collapsed on to that of the suspending fluid with simple shift factors over a wide range of particle fractions. Additional authors [40][41][42][43][44][45][46][47] investigated other types of viscoelastic suspending fluids and observed similar behavior. Using an effective shear rate concept, Ohl and Gleissle [48] formalized a general shifting procedure to collapse suspension data on to that of the suspending medium at a constant shear stress…”
Section: Introductionmentioning
confidence: 76%
“…Early work on polymer solutions by Highgate and Whorlow [39] first suggested that relative fluidities of suspensions could be collapsed on to that of the suspending fluid with simple shift factors over a wide range of particle fractions. Additional authors [40][41][42][43][44][45][46][47] investigated other types of viscoelastic suspending fluids and observed similar behavior. Using an effective shear rate concept, Ohl and Gleissle [48] formalized a general shifting procedure to collapse suspension data on to that of the suspending medium at a constant shear stress…”
Section: Introductionmentioning
confidence: 76%
“…Ref. [1]. As predicted by these models, the reduced hydrodynamic properties P p Pw=P0 (such as the apparent shear viscosity, shear moduli, etc.…”
Section: Introductionmentioning
confidence: 85%
“…To account for shear thinning, and the difference in the viscosity of the matrices, the relative viscosity (77, = q / v 0 , where qo is the viscosity of the pure matrix) was calculated and plotted, as a function of shear rate, for the four filled systems in Figs. 1 1 to 14. We suggest that the largest agglomerates in this study are formed in the composite containing 20% DVl3-PS particles in the lower molecular weight PMMA matrix; in fact, a network of particles is formed, with chains of particles connecting large agglomerates, as observed in SEM photographs of fracture surfaces of such composites. The formation of a network results in very high viscosities and highly non-Newtonian behavior.…”
Section: Effect Of Molecular Weight Of the Matrixmentioning
confidence: 99%